Supplementary Data from HAND2 Assists MYCN Enhancer Invasion to Regulate a Noradrenergic Neuroblastoma Phenotype - Man Xu (14963249) (2025)
Table S6 shows super-enhancers associated genes identified in siCtrl cells and siHAND2 cells.